Visibilidade científica e pública de mamíferos: uma abordagem usando “Culturomics” - Santos, Janisson Willames dos (2018)
The exponential technological growth and the increasing access to the Internet have transformed the amplitude, accessibility and diffusion of the information, generating a huge revolution in the availability and quality of data created by human culture and provided a unique way of understanding the impact of constant popular positions on natural environments. In this context, Culturomics emerged as the study of human culture by analyzing large amount of data and using digital techniques. Recently, its application has extrapolated its use in the social sciences, bringing new insights into the complex interaction between human and nature. Using their recent approach, we quantify the conservation research effort, the public visibility, and the threat status of global terrestrial mammal species, to understand the drivers of scientific knowledge on mammals. Our results indicate that conservation research efforts appear to have a stronger influence on the public visibility of non-threatened species. However, this same factor seems to act to promote the public visibility of data deficient species. The use of this new approach has proved useful in assessing public visibility as well as research effort on species. Nonetheless, more research needs to be done to understand the extent of public interest in mammal species and their involvement in conservation. It can help decision-makers in creating environmental policies that favor the protection of biodiversity threatened and with low social support, in addition their natural environments.